Preparation and Placement Strategy for the 2024 Election in Batu Bara - Nila Kartika Utami Abidin; Hatta Ridho; Tonny P. Situmorang (Universitas Medan Area, 2023)
This paper delves into the intricate strategy employed in the preparation and execution of the 2024 election in Batu Bara. The research utilizes a descriptive qualitative approach, facilitating the acquisition of comprehensive and lucid data, offering detailed and accurate insights into the reasons behind the unfolding events. The primary focus of this study rests on the Election Commission (KPU) of Batu Bara Regency as its object of analysis. The findings reveal a commendable and well-executed strategy in preparing and conducting the 2024 election in Batu Bara, in strict adherence to existing regulations and established timelines. The principles governing electoral arrangements are upheld, primarily supported by an information system designed to facilitate this process. However, this study also identifies areas where optimization remains incomplete. Notably, an obstacle encountered during the election preparation and placement strategy pertains to disparities between the geographical data presented in the information system and the real-world ground realities in Batu Bara Regency. These disparities warrant attention, as they introduce challenges to the seamless execution of electoral procedures.